A new iterative scheme using inertial technique for the split feasibility problem with application to compressed sensing: Suparat Kesornprom, Prasit Cholamjiak - Team, Support (Thai Journal of Mathematics, 2020)
In this work, we suggest iterative methods by using inertial term for solving splitfeasibility problem in real Hilbert spaces. We provide weak and strong convergence theoremsunder mild conditions. Finally, we apply our main result to signal recovery and give acomparison to other algorithms.